Apixaban Superior to Warfarin in Patients with Atrial Fibrillation as well as Prior Stroke or TIA - Buckley, Rita (MD Conference Express, 2012)
The recent Apixaban Compared with Warfarin in Patients with Atrial Fibrillation and Prior Stroke or Transient Ischemic Attack trial [Granger CB et al. N Engl J Med 2011; ARISTOTLE; NCT00412984] found apixaban to be superior to warfarin for stroke prevention in a wide range of atrial fibrillation (AF) patients, with significantly lower bleeding risk and lower risk of all-cause mortality [Littrell R, Flaker G. Expert Rev Cardiovasc Ther 2012]. This article results of a comparison of apixaban with warfarin in patients with AF and prior stroke or transient ischemic attack.